Pengaruh Struktur Kepemilikan, Struktur Modal, Dan Kebijakan Dividen Pada Nilai Perusahaan - Silvia Waning Hiyun Puspita Sari (Jurnal Perilaku dan Strategi Bisnis, 2018)
This study aims to examine agency theory in the Indonesian capital market. Agency conflict in this study is proxied by firm value (Tobins Q), while the agency conflict control mechanism is proxied by institutional ownership, leverage, and dividend policy. In this study the researchers examined the effect of the three endogenous variables. The data used in this study are secondary data sourced from the Indonesia Stock Exchange, Osiris, IDX, and Blommberg, namely all non-financial companies that meet the screening criteria and are listed on the Indonesia Stock Exchange in the 2010-2014 observation period. The analytical tool used in this study is multiple regression.